Structure of Bacillus subtilis superoxide dismutase - Liu, P. (International Union of Crystallography, 2007)
The sodA gene of Bacillus subtilis was expressed in Escherichia coli, purified and crystallized. The crystal structure of MnSOD was solved by molecular replacement with four dimers per asymmetric unit and refined to an R factor of 21.1% at 1.8 Å resolution. The dimer structure is very similar to that of the related enzyme from B. anthracis. Larger structural differences were observed with the human MnSOD, which has one less helix in the helical domain and a longer loop between two β-strands and also showed differences in three amino acids at the intersubunit interface in the dimer compared with the two bacterial MnSODs. These structural differences can be exploited in the design of drugs that selectively target the Bacillus enzymes.